ANALISIS PENGARUH BEBAN KERJA, HUBUNGAN INTERPERSONAL DAN SELF-EFFICACY TERHADAP STRES KERJA STAF PENDAMPING DI LINGKUNGAN DPRD PROVINSI, KABUPATEN / KOTA SE PULAU LOMBOK - Siti Hadijah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study aims to analyze the effect of partially simultaneously and determine the effect of work load, interpersonal relationship, and self-efficacy as well asto analyze the variables that have themost dominant influence on work stress assistant staff in the Provincial DPRD, Regency/City in Lombok Island. This type of researchis associative causal research and sampling technique by using proportional random sampling as much 54 staff assistant parliamentarians throughout Lombok Island. The analytical technique used is theMultiple Linear Regression. The results showed that: workload, interpersonal relationship and self-efficacy in partial and simultaneously significant effect on job stress and work load variables known to the dominant influence of work stress assistant Staff parliamentariansse Lombok Island. Keywords: Job stress, Workload, interpersonal relationships, self-efficacy.